Right hepatic artery injury: an unusual complication of penetrated duodenal ulcer disease - Espitia, Francisco Terrazas; Dávila, David Molina; Chávez, Alberto Manuel González; Gómez López, José Manuel; De Giau Triulzi, Louis Francois (International Surgery Journal, 2017)
Peptic ulcers generally appear in the stomach and the first segment of the duodenum as a result of mucosal erosion caused by pepsin and gastric acid secretion, with up to 70% of these occurring amongst patients aged 25-64. Currently, endoscopic procedures combined with proton pump inhibitors are considered the gold standard for managing complicated peptic ulcers, leaving surgical management as an option for endoscopic management failure or in scenarios such as incoercible bleeding, perforation, penetration and intestinal occlusion. Penetration of a gastric ulcer to adjacent organs is a rare complication; penetration to the liver and endoscopic diagnosis is even rarer. We have presented the case of a 54 year old diabetic male, who presented to the emergency room with upper gastrointestinal bleeding due to a chronic duodenal ulcer, with haemodynamic instability, requiring surgical management, revealing penetration to the liver with rupture of the right hepatic artery. The patient successfully recovered after surgery and was discharged 7 days after surgical intervention. We did not find any similar case reports in the current literature